Daily Exercises and Education for Preventing Low Back Pain in Children: Cluster Randomized Controlled Trial. Issue 4 (1st April 2015) - Hill, Julia J.; Keating, Jennifer L.
Abstract : Background: Children report low back pain (LBP) as young as 8 years. Preventing LBP in children may prevent or delay adult incidence. Objectives: The purpose of this study was to determine whether education and daily exercise affect LBP episodes in children compared with education alone. Design: This was a prospective, multicenter cluster randomized controlled trial. Setting: The study was conducted at 7 New Zealand primary schools. Participants: Children (n=708), aged 8 to 11 years, from 7 schools stratified by sample size (36, 114, 151, 168, 113, 45, 83) were randomized and allocated to 2 masked groups: intervention (4 schools, n=469) or control (3 schools, n=239). Interventions: Participants in the intervention group were taught 4 spinal movements for daily practice. Both groups participated in education that emphasized "back awareness." Measurements: Low back pain history at baseline was assessed. Children reported episodes of LBP during the previous week on trial days 7, 21, 49, 105, 161, and 270. Analysis was at the individual participant level, with adjustment for school clusters. Results: There were no significant differences between groups in the odds of reporting no LBP in the previous week during the study period (odds ratio [OR]=0.72; 95% confidence interval [95% CI]=0.46, 1.14; P =.16). The intervention group reported significantly fewer episodes of LBP (OR=0.54; 95% CI=0.39, 0.74; P <.001) and significantly fewer lifetime first episodes of LBP (n=86 [34%]) compared with the control group (n=58 [47%]) (OR=0.60; 95% CI=0.39, 0.91; P =.02). The odds of an episode of LBP were greater in participants with a history of LBP (OR=4.21; 95% CI=3.07, 5.78; P <.001). Low back pain episodes decreased across the trial period for both groups (OR=0.89; 95% CI=0.84, 0.95; P <.001). Adherence to exercise was poor. Limitations: Replication in other settings is needed. Conclusions: Regular exercise and education appear to reduce LBP episodes in children aged 8 to 11 years compared with education alone.